Relationships among motivation, commitment, cognitive capacities, and achievement in secondary education - Korpershoek, Hanke (Frontline Learning Research, 2016)
The aims of the present study were (1) to identify to what extent school motivation and school commitment contributed to the explanation of students’ academic achievement in addition to the effect of students’ cognitive capacities, (2) to find out whether school commitment mediated the relation between school motivation and academic achievement, and (3) to find out whether school motivation mediated the relation between school commitment and academic achievement. New in the field is that perspectives from two different research traditions were adopted, resulting in a selection of variables introduced by identity development theory and by motivational theories on achievement goals. The overall goal was to provide insight in the underlying structure of the relationships among these variables by providing new empirical evidence derived from a large student sample. A sample of more than 6,000 secondary school students from the Netherlands was therefore used in the study. Path models (structural equation models) were used to analyse the data. Fit indices of the final model were satisfactory. This model included students’ cognitive capacities, three motivation factors (performance, social, and extrinsic motivation; mastery was excluded) and one commitment component (in-depth exploration; the ‘commitment’ and ‘reconsideration of commitment’ components were excluded). The results showed small effects of performance (+), social (+), and extrinsic (-) motivation on academic achievement in addition to students’ cognitive capacities. A very small negative effect was found for in-depth exploration. In-depth exploration mediated the motivation – achievement relationships to a limited extent. Suggestions for further research are discussed.